2015
DOI: 10.1590/s0103-40142015000100005
|View full text |Cite
|
Sign up to set email alerts
|

Arqueologia e história indígena no Pantanal

Abstract: O artigo apresenta uma síntese dos dados arqueológicos sobre o Pantanal e o seu entorno, principalmente em Mato Grosso e Mato Grosso do Sul. Elaborado com base na noção de arqueologia como história indígena de longa duração, o artigo considera as trajetórias de estabelecimento e consolidação territorial da ocupação indígena regional, os processos de formação da configuração etnográfica encontrada pelos europeus e os impactos do colonialismo. O principal objetivo consiste em mostrar que a diversidade cultural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
12

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
6
0
12
Order By: Relevance
“…Social issues and use of biodiversity are linked in many ways to Points 5 and 9 of our proposed agenda for the Pantanal. Archaeological studies have found that the first human occupation in Pantanal occurred in the Initial Holocene (Bespalez, 2015), but indigenous populations existing at the time of the first European explorations in the 16th century have almost disappeared. Yet some remaining populations of Terena, Guat o, the Kadiwe´u, the Kinikinau, the Bororo, the Chiquitano, the Chamacoco, the Ishir, and the Mbya´are still present in the Pantanal (Bortolotto & Amorozo, 2012;Bortolotto, Amorozo, Guarim Neto, Oldeland, & Damasceno-Junior, 2015;Domingo & Maria, 2017;Mereles et al, 2000).…”
Section: Biodiversity and Local Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Social issues and use of biodiversity are linked in many ways to Points 5 and 9 of our proposed agenda for the Pantanal. Archaeological studies have found that the first human occupation in Pantanal occurred in the Initial Holocene (Bespalez, 2015), but indigenous populations existing at the time of the first European explorations in the 16th century have almost disappeared. Yet some remaining populations of Terena, Guat o, the Kadiwe´u, the Kinikinau, the Bororo, the Chiquitano, the Chamacoco, the Ishir, and the Mbya´are still present in the Pantanal (Bortolotto & Amorozo, 2012;Bortolotto, Amorozo, Guarim Neto, Oldeland, & Damasceno-Junior, 2015;Domingo & Maria, 2017;Mereles et al, 2000).…”
Section: Biodiversity and Local Communitiesmentioning
confidence: 99%
“…Inside Pantanal, there are also attractive sites such as the Pantanal National Park, the contrasting Amolar mountain range, the Encontro das Aguas State Park, the private reserve and its resort owned by Servic¸o Social do Come´rcio -Pantanal Bureau (SESC-Pantanal), the historical Coimbra fortress, and the paleontological site where the fossils of the oldest multicellular animal on Earth were found (Corumbella werneri), as well as other Ediacaran fauna such as Cloudina lucianoi (Adorno et al, 2018), and dolostones with stromatolites (Walde et al, 2015). Archeological sites scattered in the Pantanal have high potential impact for tourism once they are rich in rock inscriptions (petroglyphs; Bespalez, 2015;Girelli, 1994). Nonetheless, most of them are still little valued as touristic products or packages.…”
Section: Tourism As a Sustainability Inductormentioning
confidence: 99%
“…Indeed, FEM observed petroglyphs along the shoreline of Laguna La Gaiba that extend below the waterline during the dry season, demonstrating human presence at a time when lake level was lower than in the present day, potentially during the mid-Holocene. Additionally midden and cave sites from across the Pantanal suggest hunter–fisher–gatherer communities were present in the region from 5000 cal yr BP (Bespalez, 2015). However, the paucity of charcoal records in the Chiquitano region, particularly at the local scale, precludes investigation of the role of humans in influencing the fire regime at present (Maezumi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Menéndez, 1981Menéndez, -1982, entretanto, mostram que os falantes de línguas dessa família já não se encontravam nas margens do alto Madeira na época do contato com os europeus, embora ocupassem áreas relativamente próximas, a sudoeste, na região do alto Purus e dos rios Beni e Madre de Díos, na Bolívia e no Peru. Tais evidências sugerem, portanto, que centenas de anos antes do contato os grupos falantes de línguas Arawak gradualmente teriam ocupado parte da área de entorno do alto Madeira e além, como o atual estado do Acre (Schaan, 2013), os Llanos de Mojos, a Chapada dos Parecis e a Serra dos Apiacás (Heckenberger, 2008), o alto e médio Paraguai (Bespalez, 2015) e o baixo Paraná (Politis & Bonomo, 2019). Tratase, portanto, de um processo que precede a entrada dos grupos produtores de cerâmicas da Tradição Polícroma no alto Madeira.…”
Section: O Que Nos Dizem As Cerâmicas Do Alto Rio Madeira?unclassified